Charge-Exchange Byproduct Cold Protons in the Earth’s Magnetosphere - Borovsky, Joseph E.; Liu, Jianghuai; Ilie, Raluca; Liemohn, Michael W. (Frontiers in Astronomy and Space Sciences, 2022)
Owing to the spatial overlap of the ion plasma sheet (ring current) with the Earth’s neutral-hydrogen geocorona, there is a significant rate of occurrence of charge-exchange collisions in the dipolar portion of the Earth’s magnetosphere. During a charge-exchange collision between an energetic proton and a low-energy hydrogen atom, a low-energy proton is produced. These “byproduct” cold protons are trapped in the Earth's magnetic field where they advect via E×B drift. In this report the number density and behavior of this cold-proton population are assessed. Estimates of the rate of production of byproduct cool protons from charge exchange are in the vicinity of 1.14 cm-3 per day at geosynchronous orbit or about 5 tons per day for the entire dipolar magnetosphere. The production rate of cool protons owing to electron impact ionization of the geocorona by the electron plasma sheet at geosynchronous orbit is about 12% of the charge-exchange production rate, but the production rate by solar photoionization of the neutral geocorona is comparable or larger than the charge-exchange production rate. The byproduct-ion production rates are smaller than observed early time refilling rates for the outer plasmasphere. Numerical simulations of the production and transport of cold charge-exchange byproduct protons find that they have very low densities on the nightside of geosynchronous orbit and they can have densities of 0.2 - 0.3 cm-3 at geosynchronous orbit on the dayside. These dayside byproduct-proton densities might play a role in shortening the early-phase of plasmaspheric refilling.